Design and Analysis of Square and Circular type fractal Shapes Microstrip Patch Antenna (International Journal of Engineering and Computer Science, 2017)
This paper presents a design of microstrip patch antenna combining circular and square slots by cutting different slots on rectangular microstrip antenna and experimentally studied on IE3D software. This design is achieved by cutting multi shapes in square pattern combining with circular and square slots & placing a microstrip line feed. This design has been studied in III iterations. The radiation pattern of the proposed microstrip antennas maintained because of the self similarity and centro-symmetry of the fractal shapes. With fractal shapes patch antenna is designed on a FR4 substrate of relative permittivity of 4.4 and thickness 1.524mm and mounted above the ground plane at a height of 6 mm. Details of the measured and simulated results of the case-by-case iterations are presented & discussed.